Altering the rest interval during high-intensity interval training does not affect muscle or performance adaptations - Edge, J.; Eynon, N.; McKenna, M. J.; Goodman, C. A.; Harris, R. C.; Bishop, D. J. (Experimental Physiology, 2013)
It has been hypothesized that exercise-induced changes in metabolites and ions are crucial in the adaptation of contracting muscle. We tested this hypothesis by comparing adaptations to two different interval-training protocols (differing only in the rest duration between intervals), which provoked different perturbations in muscle metabolites and acid-base status. Prior to and immediately after training, 12 women performed the following tests: (1) a graded exercise test to determine peak oxygen uptake ( .VO2peak); (2) a high-intensity exercise bout (followed 60 s later by a repeated-sprint-ability test; and (3) a repeat of the high-intensity exercise bout alone with muscle biopsies pre-exercise, immediately postexercise and after 60 s of recovery. Subjects performed 5 weeks (3 days per week) of training, with either a short (1 min; HIT-1) or a long rest period (3 min; HIT-3) between intervals; training intensity and volume were matched. Muscle [H+] (155±15 versus 125±8 nmol l-1; P <0.05) andmuscle lactate content (84.2±7.9 versus 46.9±3.1 mmol (g wet weight)-1) were both higher after HIT-1, whilemuscle phosphocreatine (PCr) content (52.8±8.3 versus 63.4±9.8 mmol (g wet weight)-1) was lower. There were no significant differences between the two groups regarding the increases in .VO2peak, repeatedsprint performance or muscle Na+,K+-ATPase content. Following training, both groups had a significant decrease in postexercise muscle [H+] and lactate content, but not postexercise ATP or PCr. Postexercise PCr resynthesis increased following both training methods. In conclusion, intense interval training results in marked improvements in muscle Na+,K+-ATPase content, PCr resynthesis and VO2peak. However,manipulation of the rest period during intense interval training did not affect these changes.